Dasar Teoritik Kriminalisasi Pelaku LGBT (Analisa Ekonomi terhadap Perbuatan LGBT) - Anri Darmawan; Jeanne Darc Noviayanti Manik (UIR Law Review, 2022)
The phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) in Indonesia still seems to be an unresolved problem until now. It is even estimated that the number of LGBT groups will continue to increase. Serious efforts need to be made in tackling these sexual deviant behaviours, one of which is by criminalizing LGBT perpetrators. The existence of the LGBT group certainly has an impact, including the economic impact. This study uses a normative juridical research method. As for the formulation of the problem, namely what is the theoretical basis for criminalizing LGBT actors and how to analyze the economics of LGBT acts. The purpose of this study is to analyse and explain the theoretical basis for criminalizing LGBT actors and analyse the economic impact of LGBT acts. From this research, the theoretical basis for the criminalization of LGBT perpetrators is obtained, namely moral theory, paternalism theory and Feinberg theory. Economic analysis shows that there is discrimination against LGBT people, especially in the employment sector and international trade. The recommendation from this research is that criminal law must be responsive to the massive LGBT phenomenon in Indonesia. Criminalization is not a form of discrimination against LGBT groups, but rather an effort by the state to prioritize the main functions of criminal law, namely maintaining public morality, upholding the values ​​of Pancasila, culture, and religion.